Solid waste management regulation in the informal settlements: A social-ecological context from Kampala city, Uganda - Muheirwe, Florence; Kihila, Jacob Mabula; Kombe, Wilbard Jackson; Campitelli, Alessio (Frontiers in Sustainability, 2023)
So far, literature on solid waste management regulation in the informal settlements of Sub-Saharan African cities has yet to enlist the social-ecological context. To examine this context, we employ a mixed methods approach to collect data on waste management regulations and practices in the Makindye informal settlements. Our study reveals that multiple waste management practices are conducted simultaneously by households. Poor socio-economic status, spatial challenges and ignorance of regulations determine undesirable waste management practices such as open dumping and burning. Desirable practices such as waste sorting or recycling are neither merely practised for monetary gain nor in observance of regulation. Practices, whether desirable or not, are acquired through interactions in the community, where formal rules, as well as informal ones, are at play. Notably, most residents are unaware of waste management regulations for Kampala city or their community. Thus, some residents engage in illegal waste management practices without the inclination to commit an offence, while others adopt 'community malpractices'. However, residents are relatively more aware of informal rules than formal ones confirming the role of socialisation. We argue practices are not by instinct; therefore, while regulations shape values and norms, the reverse should also be true. Since residents are unaware of prevalent formal rules, we conclude that policymakers and enforcers may not have effectively socialised residents on regulatory instruments to transform undesired values and norms. Consequently, values and norms at the intrapersonal and interpersonal levels have influenced behaviours more than policies enforced by the government. Thus, sensitisation initiatives should focus on socialisation structures if responsive behaviours that conform to guidelines for better waste management practices are to be promoted in the informal settlements of Sub-Saharan African cities.